Analysis of Applications to Improve the Energy Savings in Residential Buildings Based on Systemic Quality Model - Fonseca i Casas, Antoni; Fonseca i Casas, Pau; Casanovas, Josep (Sustainability, 2016)
Creating a definition of the features and the architecture of a new Energy Management Software (EMS) is complex because different professionals will be involved in creating that definition and in using the tool. To simplify this definition and aid in the eventual selection of an existing EMS to fit a specific need, a set of metrics that considers the primary issues and drawbacks of the EMS is decisive. This study proposes a set of metrics to evaluate and compare EMS applications. Using these metrics will allow professionals to highlight the tendencies and detect the drawbacks of current EMS applications and to eventually develop new EMS applications based on the results of the analysis. This study presents a list of the applications to be examined and describes the primary issues to be considered in the development of a new application. This study follows the Systemic Quality Model (SQMO), which has been used as a starting point to develop new EMS, but can also be used to select an existing EMS that fits the goals of a company. Using this type of analysis, we were able to detect the primary features desired in an EMS software. These features are numerically scaled, allowing professionals to select the most appropriate EMS that fits for their purposes. This allows the development of EMS utilizing an iterative and user-centric approach. We can apply this methodology to guide the development of future EMS and to define the priorities that are desired in this type of software.